An advance care plan decision support video before major surgery: a patient- and family-centred approach. Issue 2 (18th March 2018) - Isenberg, Sarina R; Crossnohere, Norah L; Patel, Manali I; Conca-Cheng, Alison; Bridges, John F P; Swoboda, Sandy M; Smith, Thomas J; Pawlik, Timothy M; Weiss, Matthew; Volandes, Angelo E; Schuster, Anne; Miller, Judith A; et al.
Abstract : Objective: Video-based advanc care planning (ACP) tools have been studied in varied medical contexts; however, none have been developed for patients undergoing major surgery. Using a patient- and family-centredness approach, our objective was to implement human-centred design (HCD) to develop an ACP decision support video for patients and their family members when preparing for major surgery. Design and methods: The study investigators partnered with surgical patients and their family members, surgeons and other health professionals to design an ACP decision support video using key HCD principles. Adapting Maguire's HCD stages from computer science to the surgical context, while also incorporating Elwyn et al 's specifications for patient-oriented decision support tool development, we used a six-stage HCD process to develop the video: (1) plan HCD process; (2) specify where video will be used; (3) specify user and organisational requirements; (4) produce and test prototypes; (5) carry out user-based assessment; (6) field test with end users. Results: Over 450 stakeholders were engaged in the development process contributing to setting objectives, applying for funding, providing feedback on the storyboard and iterations of the decision tool video. Throughout the HCD process, stakeholders' opinions were compiled and conflicting approaches negotiated resulting in a tool that addressed stakeholders' concerns. Conclusions: Our patient- and family-centred approach using HCD facilitated discussion and the ability to elicit and balance sometimes competing viewpoints. The early engagement of users and stakeholders throughout the development process may help to ensure tools address the stated needs of these individuals. Trial registration number: NCT02489799 .